Važnost šumarske nastave i znanosti na Sveučilištu u Zagrebu za razvoj hrvatskog šumarstva : The importance of forestry education and science at the University of Zagreb for the development of Croatian forestry - Anić, Igor (Array, 2019)
This paper explores the influence of higher forestry education and forestry science at the Faculty of Forestry of the University of Zagreb on the formation and preservation of forest wealth in the Republic of Croatia during the past 120 years as the basic, authentic, self-renewable, biologically diverse and distinctly natural element. In order to do so, we shall provide a survey of some significant achievements of the faculty and its distinguished professors by citing examples of important textbooks and scientific papers. In the year 2018, the Faculty of Forestry in Zagreb marked the 120th anniversary of its establishment. It was on October 20th, 1898, that the Academy of Forestry was founded within the University of Zagreb as the first higher forestry institution in Croatia and in the south-east of Europe. The continuity of higher forestry education at the University of Zagreb has been retained to date through the periods of activity of the Academy of Forestry (1898 - 1919), the Faculty of Agriculture and Forestry (1919-1946), the Agricultural-Forestry Faculty (1946 - 1960) and the Faculty of Forestry (1960 - to date). Three characteristic periods can be singled out in the development of forestry education and science at the Faculty of Forestry in Zagreb in the course of 120 years: the first half of the 20th century, the second half of the 20th century and the first half of the 21st century. The first half of the 20th century witnessed a surge in the Croatian forestry, which can primarily be attributed to the development of higher forestry education and science at the Academy of Forestry and the Faculty of Agriculture and Forestry of the University of Zagreb. Among the most important contributions of university forestry education and science in Croatia are the establishment of the Zagreb School of Silviculture and the beginnings of organized and systematic scientific research in forestry.